Towards an Efficient Electric Pole’s Material for Iraqi Electric Network - Ameen, Sameer Hashim; Mahmood, Deyaa Mohammed Noori; Hussein, Sdaiq Aziz (Al-Nahrain Journal for Engineering Sciences, 2017)
The traditional electric poles in Iraq are usually made from steel materials. Such materials induced high weight, corrosion, permanent deformation caused by high wind speed, etc. The study aimed to numerically examine the strength of few poles made from different materials. The pole subjected to pressure developed by actual measured wind speed of 140 km/h. The numerical model of different materials and cross sections, an octagonal section electric pole made from composite material FRP–HDPE–FRP is suggested to replace the traditional one. The results showed high safety factor, approximately 5.51 besides the low ratio of high strength to weight as compared to steel materials. Using HDPE as reinforced material resulted in pole elastically deformed with only 0.222 mm. Therefore, it can be assumed that the suggested pole acts partially as a damper. Straight octagonal cross - section of pole promoted high reduction (74.22%) in maximum Von–Misses stress of that obtained in cylindrical three-stage pole. High reduction (5.87 times) in maximum deformation value was obtained when composite octagonal pole was used as compare to tapered pole made from steel.